APPLICATION OF METHODS OF COMPUTER GRAPHICS IN TECHNICAL DIAGNOSTICS OF RAILWAY ROLLING STOCK - Pulariya, A. L.; Serdyuk, M. E. (Science and Transport Progress, 2010)
The problem of processing images obtained as a result of digital photographing during the railway rolling stock technical diagnostics, using the method of skeleton interpolation, is considered.